Wind-driven rain on a building façade in urban environment. (2017) - Gao, Ge; Zhao, Lihua; Wang, Changshan; Grunewald, John; LiLi
Abstract: The amount of rain water which impinged on the building envelope has a significant effect on the building envelope's thermal performance, the indoor air humidity and the users' health and comfort. As an important exterior boundary condition, wind-driven rain (WDR) loads estimation methodology could also be used in building energy simulation (BES) and heat and moisture transport (HAM) tools. As available WDR calculation models either ignore or simplify the influence of the complicate urban environment, their results have great discrepancy with the test results on a residential building facade which is even only moderate sheltered. In this paper, systematically models are built to study the shelter effect by surrounding buildings on WDR, . The building density of the street canyon and the buildings' arrangement style of the street canyon are two parameters that had been taken into consideration. Simulation cases with three packing densities and two typical buildings' arrangements are displayed. Predominant influencing factors are pointed out.